RESIDUAL EFFECTS OF NITROGEN FERTILIZER WITH POLYMER-COATED UREA IN A CORN CROP - Mello, Tayene Franco [UNESP]; Buzetti, Salatier [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Galindo, Fernando Shintate [UNESP]; Nogueira, Lais Meneghini [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2017)
The use of nitrogenous fertilizer coated by polymers may reduce losses caused by volatilization, thus exposing this element to plants for a longer period of time. The objective of this work was to evaluate the residual effects of nitrogen in the form of conventional urea and urea coated by polymers in the production components and grain productivity of the first and second corn crops. The experiment was conducted in Selviria - MS in a clay-type Oxisol during the corn crops of 2011/12 and 2012. The experiment was arranged as a randomized block design with four replications, with a factorial 4 x 4 treatment arrangement as follows: 4 doses of N (0, 40, 80 and 120 kg ha(-1) ) and 4 forms of urea (conventional urea and urea coated by three different polymers). Treatments were applied at the time of corn sowing in the first season (2010/11) and second season (2011). The residual effects of nitrogen fertilization in the corn grown in the first crop season (2011/12) and the second crop season (2012) were then assessed. The polymer-coated urea did not differ compared to the conventional urea.
Keywords: Zea mays L.; Coated fertilizer; Nitrogen; Improved fertilizer efficiency